2021
DOI: 10.3390/molecules26216627
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Multiresidue Analysis of 65 Pesticides in Surface Water Using Solid-Phase Extraction by LC-MS/MS

Abstract: An analytical method was developed and validated for simultaneous quantitation of 65 pesticides, including one single solid-phase extraction (SPE) procedure in surface water by liquid chromatography coupled to tandem mass spectroscopy. Different parameters that have an influence on extraction efficiency were evaluated in this research. Different types of cartridges, elution solvents, and sorbent drying time were investigated, and the most appropriate one was selected. Moreover, various pretreatment techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…The mobile phase consisting only of ammonium formate as eluent additives enabled the simultaneous analysis of 480 pesticides using scheduled multiple reaction monitoring (MRM) detection in the MS/MS instrument ( Table S1 ). This eluent composition is rather different from those used earlier [ 2 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 26 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The mobile phase consisting only of ammonium formate as eluent additives enabled the simultaneous analysis of 480 pesticides using scheduled multiple reaction monitoring (MRM) detection in the MS/MS instrument ( Table S1 ). This eluent composition is rather different from those used earlier [ 2 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 26 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, both GC and HPLC analysis may be used to cover as many compounds as possible. In recent papers, the detection of 20–300 pesticides in water could be achieved if both GC-MS and LC-MS were used in the method [ 5 , 7 , 8 , 9 , 18 , 19 , 20 , 21 , 29 , 30 , 31 , 32 ]. For GC-MS analysis, the liquid–liquid extraction (LLE) of water with immiscible organic solvent such as diethyl ether or dichloromethane is a preferable approach to enrich pesticides [ 2 , 27 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is generally done using either sample ltration or centrifugation. 95 Some studies have shown that ltration is not a viable pretreatment step because some lters such as glass wool and nylon might adsorb PFASs and pesticides from water sample and therefore, reduce recovery of those compounds. [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] Also, several PFASs have been reported to leach out from some lters such as PTFE and thus can potentially contaminate samples during ltration.…”
Section: Investigation Of Potential Losses Of Ecs During Sample Prepa...mentioning
confidence: 99%
“…95 Some studies have shown that ltration is not a viable pretreatment step because some lters such as glass wool and nylon might adsorb PFASs and pesticides from water sample and therefore, reduce recovery of those compounds. [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] Also, several PFASs have been reported to leach out from some lters such as PTFE and thus can potentially contaminate samples during ltration. 50 Therefore, centrifugation was chosen to remove sediment and suspended solids from surface water samples in our study.…”
Section: Investigation Of Potential Losses Of Ecs During Sample Prepa...mentioning
confidence: 99%